Dynamics of systems to assess the environmental impact of the four most commercialized vehicles in 2018 in Brazil (Revista Brasileira de Contabilidade e Gestão, 2019)
We live in a society that has its basis of functioning and survival in mobility, the possibility ofmovement, the right to come and go, to send and receive. Therefore, the purpose of this article isto analyze the environmental impacts of the four best selling vehicles in 2018. For this, we used the system dynamics methodology through the application of modeling and computer simulation. From the elaboration of a model, scenarios of each vehicle were constructed that were evaluatedin a horizon of teen years , verifying, in each situation, the environmental impacts.
Keywords: System Dynamics; Pollution; Best Selling Vehicles